PEMBUATAN GLISEROL TRIBENZOAT DENGAN PROSES ESTERIFIKASI MENGGUNAKAN KATALIS H-ZEOLIT TERAKTIVASI OLEH ASAM KLORIDA DAN ASAM SULFAT - Mutiara Valentina M, Ekelesia Martina, Zuhrina Masyithah (Universitas Sumatera Utara, 2016)
Esterification is one method that is often used in converting glycerol. Glycerol tribenzoate is a derivative product of glycerol which used as a plasticizer for polymer industry, food additives, water repellent material on printer ink, and many more. This research aims to study the making of glycerol tribenzoate through esterification process by using natural zeolit catalyst which is activated with hydrochloric acid, in order to obtain the optimum catalyst % weight (w/w glycerol), and also to see the potential of recycling the zeolit. Zeolit is activated by 4M for 6 hours, and then calcined in the furnace at 500 oC for 5 hours. Then continued to esterification process, glycerol 90% reacted with benzoic acid which dissolved in metanol, with mole ratio of benzoic acid and glycerol at 3,5:1, reaction temperature at 65 oC, and the stirrer speed of 200 rpm, the catalyst % weight is varied at 5 %, 6%, 7%, and 8%, and catalyst recycling is performed 3 times. FTIR characterization result a close match, shows that the product is glycerol tribenzoate. The highest yield of zeolite which activated by HCl is obtained at 6% catalyst % weight i.e 68,992%, while zeolite that activated by H2SO4 is obtained at 8% catalyst % weight i.e 69,678%, H- zeolit catalyst is still feasible to use up to 3 times recycling, with percent of yield reduction for each recycle is ≤ 8%.